Investigation fatigue crack initiation and propagation cruciform welded joints by extended finite element method (XFEM) and implementation SED approach (Fracture and Structural Integrity, 2022)
This study has used the strain energy density (SED) approach to evaluate the stress intensity factor (SIF) of cracked cruciform welded joints in Hardox 450 steel. A microstructural analysis was made of Hardox 450 steel which is composed of refined and tempered low carbon martensite. The obtained results of simulation will be compared with those provided by J-integral methode for different enriched zones and contours based on the extended finite element method (XFEM) coupled with the level set technique (LST).  Crack initiation and propagation under cyclic loading have been adopted for the modeling of cruciform welded joints.
Keywords: Strain energy density approach; XFEM; Stress intensity factor; Crack initiation and propagation; Hardox 450